Classification of Islamic social enterprises (ISE) in Malaysia based on economic sectors / Muhammad Iqmal Hisham Kamaruddin and Sofiah Md Auzair - Kamaruddin, Muhammad Iqmal Hisham; Md Auzair, Sofiah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
Based on Islamic social enterprise (ISE) concept which is a combination of both social and economic objectives embedded with Islamic principles and values, this study aims to classify ISE based on economic sectors namely public, private and non-profit sectors. In addition, eight organisations that represent ISEs in Malaysia are also being discussed in order to support the classification of ISE based on economic sectors. In order to examine these eight ISEs, this study reviews professional documents, online information and comprehensive literature to analyse selected ISEs in Malaysia. Based on findings, this study concludes that ISEs in Malaysia can be classified based on all three economic sectors identified. Therefore, this study contributes to the body of knowledge as the first study made in examining and exploring classification of ISEs based on economic sectors specifically within Malaysia context. Besides, this study also among the pioneer studies on ISE itself.